Learn Rails 5.2 Accelerated Web Development with Ruby on Rails - Wintermeyer, Stefan (Apress, 2018)
Learn to build Rails-based web applications using all the latest features offered in Rails 5.2. Author Stefan Wintermeyer begins by teaching the basics of Ruby 2.5 before proceeding through all aspects of Rails, utilizing clean, succinct examples - rather than a single large application. This book covers topics including Active Storage, Credentials, Active Record, Scaffolding, REST, Routing, Bundler, Forms, Cookies, and Sessions, all of which are vital for modern Rails web applications. To complement these topics you'll also learn about test-driven development, Action Cable, Active Job, Action Mailer, I18n, Asset Pipeline, and caching. Finally, you'll see a how-to for a production web server with nginx. This complete set of skills will set you up for a future of efficient and elegant Rails coding. You will: Use the Ruby on Rails web development framework Install and manage the Rails framework Persist data for your web application with Active Record Work with forms Apply a test-driven development approach to your Rails-based web applications Discover many Rails secrets and tips .